CONSIDERATIONS ABOUT THE ELDERLY FRAILTY CONDITION: A REVIEW ARTICLE (Fiep Bulletin - online, 2013)
The current study has as a goal analyzing current trends of publications and developed studies about fragile elderly, frailty in aged and geriatric nursing. Descriptive study of a literature review type performed through bibliographic lifting up in electronics data bases LILACS, SCIELO e BDENF. As descriptors, it was used “fragile elderly”, “frailty in elderly” and “geriatric nursing” whereof it were found, respectively, 88, 17 e 355 articles; it was performed a historic cut including published studies in the period from 2003 to 2008. From 460 found articles, 90 made part of the sample, where the biggest part was published in Portuguese. The more frequently focused theme was hospital care, continuing by professional education, AVD accomplishments and reflections about the aging process. In a general way it is observed at this study which there is a trend in the considered years about an increasing of studies number and publications in human aging area as for the analyzed thematic, Frailty in elderly. It was concluded which the frailty in elderly is an emerging thematic, therefore, the considerations performed by the studies of this area should be divulged so that there is theme comprehension by all those responsible for the elderly's care, making it easier factors' identifications that lead to the frailty and, thus, put it off at maximum its occurrence.
Keywords: Aging; Frail Elderly; nursing